The 29 July 2021 MW 8.2 Chignik, Alaska Peninsula Earthquake Rupture Inferred From Seismic and Geodetic Observations: Re‐Rupture of the Western 2/3 of the 1938 Rupture Zone. Issue 4 (18th February 2022) - Liu, Chengli; Lay, Thorne; Xiong, Xiong
Abstract: On 29 July 2021, an M W 8.2 thrust‐faulting earthquake ruptured offshore of the Alaska Peninsula within the rupture zone of the 1938 M W 8.2 earthquake. The spatiotemporal distribution of megathrust slip is resolved by jointly inverting regional and teleseismic broadband waveforms along with co‐seismic static and high‐rate GNSS displacements. The primarily unilateral rupture expanded northeastward, away from the rupture zone of the 22 July 2020 M W 7.8 Shumagin earthquake. Large slip extends along approximately 175 km, spanning about two third of the estimated 1938 aftershock zone, with well‐bounded depth from 20 to 40 km, and up to 8.6 m slip near the hypocenter. The rupture terminated in the eastern portion of the 1938 aftershock zone in a region of very large geodetic slip deficit where peak slip appears to have occurred in the 1938 rupture. The 2021 and 1938 events do not have similar slip distributions and do not indicate persistent asperities. Plain Language Summary: A great earthquake ruptured along the plate boundary between the underthrusting Pacific plate and the North American plate seaward of the Alaska Peninsula. GNSS measurements along the peninsula had indicated prior strain accumulation offshore in the region where slip occurred. The last large earthquake in this region ruptured in 1938 with the same magnitude of 8.2. That rupture appears to have extended further northeast along the plate boundary and had its peak slip in a region beyond the 2021 rupture. The plate boundary to the southwest recently ruptured in the M W 7.8 Shumagin earthquake of 22 July 2020, and the 2021 slip zone does not overlap significantly with the adjacent rupture. Slip of up to 8.6 m occurred at depths from 20 to 40 km during the 2021 event, larger than the slip deficit that could have accumulated from 1938 to 2021 (approximately 5.2 m). Aftershock activity was most intense in the shallower half of the main slip patch adjacent to the peak slip region, but the overall earthquake sequence has unusually low aftershock numbers. Before the rupture, the rupture zone had a decadal decrease in b ‐value, the slope of the Gutenberg‐Richter magnitude distribution, which is consistent with a stress build‐up. The 2021 event is not a repeat of the 1938 earthquake, indicating an inhomogeneous stress accumulation. Key Points: The 29 July 2021 M W 8.2 earthquake involved thrust faulting in the western two‐third of the 1938 Alaska Peninsula earthquake aftershock zone Joint inversion of seismic and GNSS data for the slip history resolves a main slip patch distributed from 20 to 40 km deep The 2021 and 1938 ruptures are not simple repeat events; the large‐slip region in 1938 is offset from the large‐slip region in 2021